City profile: Pune, India. (April 2016) - Krishnamurthy, Rashmi; Mishra, Rajeev; Desouza, Kevin C.
Abstract: Cities around the globe are urbanizing at a fast rate and are facing the critical challenges of managing economic development and inclusive growth. This scenario is particularly troublesome in developing countries where secondary cities are growing at an unprecedented rate but lack the institutional capacity to manage urbanization. Secondary cities are tier II cities below primary cities in the urban hierarchy. To examine the unique challenges and opportunities facing secondary cities, we trace Pune's urban growth. Pune is the second largest city in the state of Maharashtra, India and is emerging as an industrial and educational hub. The presence of large industrial and educational sectors has resulted in massive urban population growth, including a large migrant population from rural areas. This massive growth is straining Pune's critical infrastructures. First, we trace Pune's urban history in terms of social, economic, administrative, and environmental planning and development. Second, we examine key urban challenges faced by the city. We find that while the city of Pune is moving towards becoming a megacity, it still has a chance to change its trajectory to become one that is more sustainable, equitable, and just. However, to evolve into a sustainable and equitable city, Pune's urban planners need to pay careful attention to several urbanization issues. This profile offers insights regarding the unique challenges faced by secondary cities in developing countries and discusses policy implications to transform secondary cities into catalysts for economic growth and development. Highlights: Cities around the globe are urbanizing at a fast rate, and this scenario is particularly troublesome in developing countries where secondary cities (tier II cities below primary cities in the urban hierarchy) are growing at an unprecedented rate. In this profile, we examine the unique challenges and opportunities faced by the city of Pune, India – a secondary city that is emerging as an industrial and educational hub. We trace Pune's urban history in terms of social, economic, administrative, and environmental planning and development to highlight the efforts undertaken by the administrators are for managing and redesigning the urban sphere. While, the city Pune is investing significant resources and developing master plans and guidelines for addressing key urban challenges, yet the city also faces several challenges, particularly in terms increase in environmental degradation, social segregation, and erosion of institutional capacity to manage and govern urban growth. The profile discusses policy implications for transforming secondary cities into catalysts for economic growth. Towards this end, city planners need to develop an integrated system of cities, which promotes public-private partnerships for providing services, improves critical infrastructures, develops institutional and management capacities, and reduces social fragmentation, and fosters cities as growth nodes.